THE IMPACT OF SOCIAL MEDIA ON THE IDENTITY CONSTRUCTION OF MULTILINGUAL STUDENTS - Fadillah, Ahmad Arif; Gumilar, Gugum (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
Social media has become an integral part of the lives of students, particularly those from multilingual backgrounds. This study examines the influence of social media on the identity construction of multilingual students. Adopting a qualitative approach, the researchers interviewed high school students in Indonesia to gain insights into the key factors driving their engagement with mainstream culture through social media use, as well as the subsequent impact on their investment in learning the language of the dominant culture. The findings reveal that the perceived ideologies of social media, the validation of linguistic and cultural capital, and the representation of desired identities are the primary motivational forces behind the students' multilingual social media engagement. Interestingly, the study also found that the students' multilingual social media engagement reshaped their acculturation expectations, attitudes, and access to resources, which in turn influenced their investment in learning and using foreign language, both on social media and in their daily lives.